If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -2y)(5x + y) = 0 Multiply (3x + -2y) * (5x + y) (3x * (5x + y) + -2y * (5x + y)) = 0 ((5x * 3x + y * 3x) + -2y * (5x + y)) = 0 Reorder the terms: ((3xy + 15x2) + -2y * (5x + y)) = 0 ((3xy + 15x2) + -2y * (5x + y)) = 0 (3xy + 15x2 + (5x * -2y + y * -2y)) = 0 (3xy + 15x2 + (-10xy + -2y2)) = 0 Reorder the terms: (3xy + -10xy + 15x2 + -2y2) = 0 Combine like terms: 3xy + -10xy = -7xy (-7xy + 15x2 + -2y2) = 0 Solving -7xy + 15x2 + -2y2 = 0 Solving for variable 'x'. Factor a trinomial. (3x + -2y)(5x + y) = 0Subproblem 1
Set the factor '(3x + -2y)' equal to zero and attempt to solve: Simplifying 3x + -2y = 0 Solving 3x + -2y = 0 Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 3x + -2y + 2y = 0 + 2y Combine like terms: -2y + 2y = 0 3x + 0 = 0 + 2y 3x = 0 + 2y Remove the zero: 3x = 2y Divide each side by '3'. x = 0.6666666667y Simplifying x = 0.6666666667ySubproblem 2
Set the factor '(5x + y)' equal to zero and attempt to solve: Simplifying 5x + y = 0 Solving 5x + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 5x + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 5x + 0 = 0 + -1y 5x = 0 + -1y Remove the zero: 5x = -1y Divide each side by '5'. x = -0.2y Simplifying x = -0.2ySolution
x = {0.6666666667y, -0.2y}
| x^2+4xy=19 | | 2x=2x+14 | | (5-x/2)=-4 | | 3(m+5)-6=3(m-3) | | (5-x/2)=-14 | | 3x+2y=4800 | | 5-x/2=-4 | | F=(28+3S)KN | | 5y-8+y=1 | | 2x+6=4x+9 | | 5y-8-y=1 | | 2x+6=4+9 | | 5x=x+t | | 9X+5Y=-56 | | X+xy+y=21 | | 3x+8=-4+71 | | 7=-3-4b | | 5u+5(1-6)=u+8 | | 5x-3=6x+2x-9 | | 2cos^2(x)-sin(x)=0 | | 4*ln(x)-x=6 | | -3+6=2x-9 | | X^5/3=0.5 | | 10x-7(3)=-18 | | 17a-4= | | 4(3x-8)=28 | | 16y-10=14 | | 1/3(6x=2x | | 8x+8=3x+73 | | 3ln(2x+1)-5=1 | | (3x-x)+(8x+9)= | | x^3-2x^2+36=0 |